2006
DOI: 10.1159/000093121
|View full text |Cite
|
Sign up to set email alerts
|

Is Endometriosis Associated with Systemic Subclinical Inflammation?

Abstract: Endometriosis is a pelvic inflammatory process with altered function of immune-related cells and increased number of activated macrophages in the peritoneal environment that secrete various local products, such as growth factors and cytokines. The elevation of cytokines and other factors in the peritoneal fluid is accompanied by the elevation of similar factors, such as CRP, SAA, TNF-α, MCP-1, IL-6, IL-8 and CCR1, in the peripheral blood of patients with endometriosis. CD44+ and CD14+ monocytes are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
132
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 125 publications
6
132
0
9
Order By: Relevance
“…1 There is general agreement that endometriosis is a pelvic inflammatory process; however, research has suggested that endometriosis is also characterized by systemic inflammation. 4,5 Various kinds of inflammatory factors have been found to be elevated in peritoneal fluid and in the peripheral blood among women with endometriosis compared with controls. [5][6][7][8] Several case-control studies have found that women with endometriosis had higher serum levels of low-density lipoprotein (LDL) or oxidized LDL compared with controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 There is general agreement that endometriosis is a pelvic inflammatory process; however, research has suggested that endometriosis is also characterized by systemic inflammation. 4,5 Various kinds of inflammatory factors have been found to be elevated in peritoneal fluid and in the peripheral blood among women with endometriosis compared with controls. [5][6][7][8] Several case-control studies have found that women with endometriosis had higher serum levels of low-density lipoprotein (LDL) or oxidized LDL compared with controls.…”
mentioning
confidence: 99%
“…4,5 Various kinds of inflammatory factors have been found to be elevated in peritoneal fluid and in the peripheral blood among women with endometriosis compared with controls. [5][6][7][8] Several case-control studies have found that women with endometriosis had higher serum levels of low-density lipoprotein (LDL) or oxidized LDL compared with controls. [9][10][11] It is possible that chronic inflammation, such as that associated with endometriosis, could impact lipid metabolism through various mechanisms and lead to high LDL levels 12,13 -the primary form of hypercholesterolemia.…”
mentioning
confidence: 99%
“…17,18 The resulting fibrosis and stricture formation may be the reason behind most intestinal endometriosis lacking the classical cyclical abdominal pain during menstrual cycle.…”
Section: 13mentioning
confidence: 99%
“…Endometriosis is often accompanied by marked changes in the number and function of inflammatory products, including human neutrophil peptides belonging to the α-defensin family (11), macrophage migration inhibitory factor (MIF) (12), C-C chemokine monocyte chemoattractant protein-1 (MCP-1), serum amyloid A (SAA), TNF-α, IL-1, IL-6, IL-8, chemokine (C-C motif) receptor 1 (CCR1) (13) and regulated on activation, normal T cell expressed and secreted (RANTES) (14). Defensin is involved in innate immunity against bacteria and kills microbes.…”
Section: Innate Immunity and Inflammation In Endometriosismentioning
confidence: 99%